2012
DOI: 10.1002/cbic.201200389
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Photoaffinity‐Based Probe for Selective Detection of Cathepsin L Active Form

Abstract: Detecting the active forms of proteases by using activity-based probes in complex proteomes has become an intensively investigated field of research over the past years because many pathogenic conditions involve alterations in protease activities. The detection of lysosomal cysteine proteases, the cathepsins, has mostly relied on the use of probes that incorporate reactive electrophilic moieties to modify a cysteine in the active site covalently. Here we report the first example of an activity-based probe that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…They bind proteins non-covalently (affinity based solely on non-covalent interactions) first and form a non-selective covalent bond with the closest amino acid residue only upon irradiation. Torkar et al took advantage of this technique and developed the first photoaffinity-based probe (Entry P3, Table 3) to detect active cathepsin L selectively over other members of the family [170]. The photoaffinity-based probe was designed based on existing peptidyl acetyloxymethyl ketone (AOMK), a known covalent modifier of cysteine proteases.…”
Section: Photoaffinity-basedmentioning
confidence: 99%
See 1 more Smart Citation
“…They bind proteins non-covalently (affinity based solely on non-covalent interactions) first and form a non-selective covalent bond with the closest amino acid residue only upon irradiation. Torkar et al took advantage of this technique and developed the first photoaffinity-based probe (Entry P3, Table 3) to detect active cathepsin L selectively over other members of the family [170]. The photoaffinity-based probe was designed based on existing peptidyl acetyloxymethyl ketone (AOMK), a known covalent modifier of cysteine proteases.…”
Section: Photoaffinity-basedmentioning
confidence: 99%
“…To address this issue, Dana et al adopted a previously reported peptidyl vinylsulfonate inhibitor KD-1-a highly potent, selective, covalent and irreversible inhibitor of cathepsin L discussed in Section 3.7-and tactically appended a small alkynyl group at the para-position of the Cbz group [117]. This led to the development of a clickable and tagless activity-based probe (catABP) of cathepsin L that retained the key desirable traits of KD-1; i.e., cell permeability, charge profile, molecular weight, potency and selectivity profile [170]. This strategy eliminated the requirements of including bulky and charged fluorophore/quencher moiety to the probe.…”
Section: Clickable and Taglessmentioning
confidence: 99%
“…Cysteine Protease (Cathepsin). Torkar et al 389 reported a complementary photoinduced ABP method toward cysteine protease cathepsins. Electrophilic ABPs are widely used to profile this enzyme class; however, it would be preferable to find probes selective for certain individual classes such as cathepsin L (Cat-L).…”
Section: Chemical Reviewsmentioning
confidence: 99%
“…These concerns are mitigated with highly selective probes, which have been discovered for CTL activity by screening combinatorial substrate libraries, [14c,25] typically requiring generation and testing of thousands to hundreds of thousands of compounds [26] . Although highly selective, these probes often lack fluorescence quenching mechanisms [22a–c] and therefore provide bright labeling but poor contrast until inactive probes are washed out of the sample; [17,25a,27] this compromises their use in rapid and single‐step detection.…”
Section: Figurementioning
confidence: 99%